The evolution of ASEAN's language policies: A diachronic analysis of official documents and website. - Chen Zhang; Ronghui Zhao; Yan Huang (PLoS ONE)
Language policy plays a pivotal role in sustaining language behaviors and transforming language ideologies into practices. While the analysis of language policies in international organizations has received increasing attention, the evolution of language policies in the Association of Southeast Asian Nations (ASEAN) has been understudied. Existing research on ASEAN's language policies has concentrated on its official language, often overlooking the language practices and ideologies embedded within these policies. This study seeks to investigate the evolution of ASEAN's language policy by examining its official documents and website. We employed the Wayback Machine to trace the development of the ASEAN official website and adopted a corpus-based approach, utilizing tools such as AntConc and Sketch Engine, to analyze the Chairman's Statements of the ASEAN Summit (CSAS). The study reveals three key insights: 1) The evolution of the ASEAN official website can be categorized into three distinct stages. 2) A consistent use of the collective pronoun "we" in the statements highlights the emphasis on cooperation and progress across economic and political-security domains. 3) The ASEAN community has persistently upheld its values, fostering an ASEAN identity and a genuine ASEAN community throughout its development. This diachronic analysis clarifies the characteristics of ASEAN's language policy, deepening our understanding of the intricate relationship between language practices and ideology, and their implications for regional cooperation and integration.